2018
DOI: 10.1007/s00167-018-4872-z
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-stabilized inserts are preferable to cruciate-substituting ultracongruent inserts due to more favourable kinematics and stability

Abstract: Therapeutic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…Despite the kinematic differences, studies have found equivalent clinical outcomes between PS TKA and UC inserts. 47,49,50,55,56 Some studies have also shown that UC inserts have comparable clinical outcomes to cruciate retaining TKA. 54,5759…”
Section: Ultracongruent Insertsmentioning
confidence: 99%
“…Despite the kinematic differences, studies have found equivalent clinical outcomes between PS TKA and UC inserts. 47,49,50,55,56 Some studies have also shown that UC inserts have comparable clinical outcomes to cruciate retaining TKA. 54,5759…”
Section: Ultracongruent Insertsmentioning
confidence: 99%
“…One previous cadaver study compared the biomechanics of intact, CR and CS TKR during simulated stair‐descent loading, and noted a substantial anterior femoral shift of the CS TKR knees (without a PCL), which agrees with the current study. Generally speaking, however, most clinical studies have found that there is little to no difference in the clinical outcomes of CR bearings with a PCL versus CS (or ultra‐congruent) bearings without a PCL . The fact that findings from in vitro cadaver studies do not seem to present clinically in the form of any functional disability may be due to simplifications and abstractions from the real loading scenario; or, on the clinical side, insensitivity to relatively small changes in joint laxity or post‐operative muscle compensation to stabilize the knee.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, biomedical device manufacturers have offered increased‐stability implants for patients with cruciate ligamentous deficiency, which employ more congruent condylar surfaces rather than a traditional cam‐post mechanism, referred to by some as “Ultracongruent” (Zimmer‐Biomet, Aesculap), “Deep Dished” (Smith and Nephew), or “Condylar‐Stabilized” (Stryker). Previous studies disagree on the efficacy of these bearing designs, especially in regards to their ability to provide normal knee stability …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High quality studies have scores of 4–8, whereas low quality studies have scores of 0–3. [ 17 ] For the Newcastle-Ottawa Scale, as recommended by the Cochrane Non-Randomized Studies Methods Working Group, we assessed studies based on 3 criteria: selection of the study groups, comparability of the groups, and ascertainment of either the exposure or the outcome of interest for case-control and cohort studies. The maximum score observed was 9 points, and total scores lower than 4 points were considered low in quality.…”
Section: Methodsmentioning
confidence: 99%